2018
DOI: 10.18488/journal.31.2018.51.14.22
|View full text |Cite
|
Sign up to set email alerts
|

Financial Efficiency of India Tourism Development Corporation (ITDC) Limited: An Empirical Study

Abstract: Article History

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 2 publications
1
16
0
1
Order By: Relevance
“…Cockburn, Henderson, and Stern [9] reported further that China was likely to be the largest beneficiary as it dominates the AI market in Asia-Pacific by as high as 70 percent. These findings concur with those that were established by Cohen [10], who held AI-enabled automated transportation responsible for this increase; or by De Backer, DeStefano, Menon, and Suh [11] who also confirmed that China was likely to embrace fleet-wide traffic flow through AI applications, hence elevating congestion levels [1,[12][13][14][15][16][17][18].…”
Section: Literature Reviewsupporting
confidence: 88%
“…Cockburn, Henderson, and Stern [9] reported further that China was likely to be the largest beneficiary as it dominates the AI market in Asia-Pacific by as high as 70 percent. These findings concur with those that were established by Cohen [10], who held AI-enabled automated transportation responsible for this increase; or by De Backer, DeStefano, Menon, and Suh [11] who also confirmed that China was likely to embrace fleet-wide traffic flow through AI applications, hence elevating congestion levels [1,[12][13][14][15][16][17][18].…”
Section: Literature Reviewsupporting
confidence: 88%
“…These systems enable users to realize the status of the performance in the supply chain such as strengths, weaknesses, and the levels of current performance in order to allow companies to make informed decisions towards the opportunities and threats. Organizations are able to take appropriate actions at the right time (Christopher, 2011) to effectively improve their performance (Nasiri et al, 2010;Solomon et al, 2014;Castorena et al, 2014;Dim & Ezeabasili, 2015;Angbre, 2016;Wang & Lu, 2016;Purnama, 2014;Nazal, 2017;Tanoos, 2017;Maldonado-Guzman, et al, 2018;Taqi et al, 2018).…”
Section: Supply Chain Operational Performancementioning
confidence: 99%
“…Supply chain has central importance for every business activity (Peng et al, 2016;Quarshie et al, 2016;Richter & Walther, 2016). These activities play crucial role in customer satisfaction (Duru & Chibo, 2014;Purnama, 2014;Nazal, 2017;Taqi et al, 2018;Nadeem et al, 2018) which may have significant effects on sustainable business outcomes. In this competitive environment, companies are moving towards higher performance of supply chain activities.…”
Section: Introductionmentioning
confidence: 99%